Corneal biomechanical properties after laser-assisted in situ keratomileusis and photorefractive keratectomy - Hwang ES (Dove Medical Press, 2017)
Eileen S Hwang,1 Brian C Stagg,1 Russell Swan,1 Carlton R Fenzl,1 Molly McFadden,2 Valliammai Muthappan,1 Luis Santiago-Caban,1 Mark D Mifflin,1 Majid Moshirfar1,3 1Department of Ophthalmology and Visual Sciences, John A. Moran Eye Center, 2Department of Internal Medicine, University of Utah, Salt Lake City, 3HDR Research Center, Hoopes Vision, Draper, UT, USA Background: The purpose of this study was to evaluate the effects of laser-assisted in situ keratomileusis (LASIK) and photorefractive keratectomy (PRK) on corneal biomechanical properties.Methods: We used the ocular response analyzer to measure corneal hysteresis (CH) and corneal resistance factor (CRF) before and after refractive surgery.Results: In all, 230 eyes underwent LASIK and 115 eyes underwent PRK without mitomycin C (MMC). Both procedures decreased CH and CRF from baseline. When MMC was used after PRK in 20 eyes, it resulted in lower corneal biomechanical properties at 3 months when compared to the other procedures, but all three procedures had similar values at 12 months.Conclusion: Significant but similar decreases in corneal biomechanical properties after LASIK, PRK without MMC, and PRK with MMC were noted. Keywords: corneal biomechanics, photorefractive keratectomy, laser-assisted in situ keratomileusis, corneal hysteresis, corneal resistance factor, mitomycin C